Considerations about the grotesque in the Popular Puppetry of Brazilian Northeast (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
The poetic of the Popular Puppetry of Brazilian Northeast (Teatro de Bonecos Popular do Nordeste/T.B.P.N.) explores the grotesque element in a parodic way, as a resource of comicity – and a very Brazilian comicity. Based on the relationship between the ideas of Bakhtin (1993) and Propp (1992) and data collected by the research Change and Pemanence in Contemporary Mamulengo, this paper indicates how the grotesque dimension of the popular imagination remains alive in the visuality and theatrical games of this genre of Puppet Theatre.
Keywords: popular comedy; puppet theatre; mamulengo’s theatre